1975
DOI: 10.1021/jf60200a020
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbit root starches. Isolation and some properties of starches from Cucurbita foetidissima and Cucurbita digitata

Abstract: Nujol mull spectrum indicated O-H stretching vibrations of intermolecular polymeric associations via hydrogen bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…The gelatinization temperature was determined to be 64.5-67.5 °C by observation of staining with Congo Red. Gelatinization temperatures very close to this range have been reported for other cucurbit starches (Berry et al, 1975;Reichert, 1913).…”
Section: Resultssupporting
confidence: 78%
“…The gelatinization temperature was determined to be 64.5-67.5 °C by observation of staining with Congo Red. Gelatinization temperatures very close to this range have been reported for other cucurbit starches (Berry et al, 1975;Reichert, 1913).…”
Section: Resultssupporting
confidence: 78%
“…Bemis et al (1) discussed the composition of the seed oil. The perennial plants also develop large tuberous roots which contain 55% starch on a moisture equilibrated basis (8). The distribution of the species, growth habits, morphology, and mode of reproduction were described by Bemis et al (1).…”
Section: Introductionmentioning
confidence: 99%
“…Although the major economic potential of the species lies in its ability to produce oil and protein rich seeds, Berry et al (1975) reported the presence of root starch in potentially commercial quantity. The plant develops a large perennial tuberous root, presumably used for water storage (Dittmer and Talley, 1964).…”
mentioning
confidence: 99%
“…Three-year-old roots often reach depths of 1 to 2 m, with crown diameters of 20 to 30 cm. By an extractive procedure, 55% (dry weight basis) of the ground whole root was recovered as starch (Berry et al, 1975).…”
mentioning
confidence: 99%